MODERN PATRONS OF GOOD DEATH: A CATHOLIC RESPONSE TO THE NOTIFICATION OF THE SUPREME COURT OF INDIA ON EUTHANASIA - Vechoor, Dominic (Asian Horizons, 2015)
This is a moral theological response to the bio-ethical question of euthanasia in the light of the post Vatican II teachings and the latest theological developments in the Church. The complex moral issue of mercy killing is particularly explored in the special context of the notification of the Supreme Court of India in July 2014, a first step towards legalizing passive euthanasia in India. For a Christian response, the biblical, patristic, liturgical and magisterial roots of the dignity of human life and person are clearly analyzed in this article. The morality of the withdrawal of treatment and the Christian meaning of human suffering and death are also well explored here. A few pastoral recommendations are suggested at the end of the article. Our study makes it clear that only by a genuine ‘reading of the signs of the times’ and ‘going back to the sources,’ two important proposals of Vatican II, we can have a realistic and solid response to the different moral issues of today and the integral renewal of the Church, for which the Vatican II made the clarion call.